EFFECTIVENESS OF EDUCATIONAL VIDEOS ON PREGNANT WOMEN’S AWARENESS OF EXCLUSIVE BREASTFEEDING - Nunik Hindriyani; Kartika Adyani; Hanifatur Rosyidah (Jurnal Kesehatan Kusuma Husada, 2026)
Background: Video health promotion media is essential for improving mothers’ knowledge about exclusive breastfeeding. A preliminary study conducted at Anugerah Pekalongan Hospital on December 26-27, 2024, revealed that midwives often fail to educate mothers due to high patient volumes and limited staff. Interviews with 15 pregnant women revealed that 80% had never received information about exclusive breastfeeding, and only 20% received information about exclusive breastfeeding from pregnancy classes, ANC sessions with midwives, and social media. This study aimed to assess the impact of video educational materials on mothers’ understanding of exclusive breastfeeding at Anugerah Pekalongan Hospital.Methods: A quantitative research employing a pre-experimental method and a design involving one group with pretests and posttests. The participants included primigravida pregnant women who attended and received ANC check-ups at Anugerah Pekalongan Hospital. A technique of random sampling was employed with 38 participants.Results: Video educational media successfully enhanced pregnant women's understanding of exclusive breastfeeding at Anugerah Pekalongan Hospital. Data processing with SPSS confirmed this, yielding a p-value of 0.000, which is less than 0.05.Conclusion: Expectant mothers should use educational videos on exclusive breastfeeding to enhance their understanding of it, allowing them to exclusively breastfeed their infants